Digital Interactivity and Its Presence in Spanish Cultural Institutions - Martínez Sanz, Raquel (Revista del CLAD Reforma y Democracia, 2017)
Museums are cultural institutions, and mostly public, whose modern conception entails the priority of spreading the artistic and/or heritable testimonies that treasures, this way making users become participants. By means of hypermedia language, suitable to make text, image and sound converge in a single space; the museum stimulates the user´s participation, mainly in-person. Moreover, with the advent of the Internet, interactivity extends to the virtual realm and becomes more accessible.This article examines the evolution of the usage of hypermedia language in the museum, as it is aimed at enhancing the museum's communicative and educational functions. Likewise, the results and difficulties found under its implementation have been described. Additionally, an exploratory empirical study on the main museums of contemporary art in Spain has been carried out. Such research analyzes the functionality and dynamics of three online interactive services, characterized by stimulating the understanding of the artwork as well as having a strong intrinsic participatory component. We refer to the collection online, QR-codes and games online.The results reveal that Spanish museum institutions are still far from exploiting the full potential out of the Net, despite the direct benefits this would entail: gaining visibility, reaching a higher number of targets, or fostering collaborative intelligence.This paper also aims to draw attention to the current management policies in cultural institutions; centers that belong to the entire community, and in which users have already expressed their desire to participate, not only in- person, but also in a virtual form.
Keywords: Cultural Policy; Technological Change; Relations with Customers; Museums; Knowledge Management; Spain